Systemic Nutrition: What's YOUR Gut Reaction? - Escott-Stump, Sylvia (East Carolina University, 2008)
Presentation accompanying lecture for receiving the Lenna Frances Cooper Award at the 2008 Food and Nutrition Conference and Exhibition of the American Dietetic Association
Keywords: MTHFR deficiency; L-methylfolate; Nutritional genetics